PENGARUH DAYA TARIK IKLAN DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PENGGUNA JASA TRANSPORTASI PADA PT. PUTRA HANDAYANI TRANS (PHD) - Andik Ruswandriyo; Sri Wahyuni Mega; Diana Ambarwati (Cahaya Ilmu Bangsa, 2024)
This research aims to determine the influence of advertising attractiveness and service quality on decisions to use transportation services at PT. PHD Trans. The research method used is a quantitative method with a descriptive approach. Data collection in this research was carried out by distributing questionnaires to transportation service users at PT. PHD Trans and calculated using the SPSS Version 25 application. The population in this study was 450 service users and the sample was 212. Data analysis techniques used included Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression Analysis, T Test, F Test , and Test of the Coefficient of Determination R2. In the Validity Test, it is known that all question items (X1, X2, and Y) have a significance value of 0.000 < 0.05 so that each variable is declared valid. Then in the Reliability Test each variable was declared reliable because it had a Cronbach's Aplha value > 0.60. Then, in the t test, it is known that the variables of advertising attractiveness (X1) and service quality (X2) have a significance value of 0.000 <0.05 so that these two variables partially have a significant effect on the decision to use the service. Then the F test shows that the significance value is 0.000 < 0.05, which shows that the attractiveness of advertising and service quality simultaneously influence the decision to use transportation services at PT. Putra Handayni Trans (PHD).